Design of fluorescent polymeric thermometers based on anthrapyrazolone functionalized oligo(ethylene glycol) methacrylates. (20th March 2023) - Saravanan, S.; Babu, Anashwara; Merckx, Ronald; Zhong, Zifu; Anandan, Mageshwari; Nutalapati, Venkatramaiah; De Geest, Bruno G.; Hoogenboom, Richard; Jerca, Valentin Victor; Maji, Samarendra
Abstract : Oligo(ethylene glycol) methacrylates functionalized with anthrapyrazolone are reported as fluorescent polymeric thermometers with a broad linear temperature sensing regime. Abstract : Temperature is one of the most important parameters for a wide range of applications, including biological and chemical systems, because it affects cellular activity by controlling metabolic processes within the cells as well as molecular diffusion and reaction kinetics. The anthrapyrazolone moiety has been used in a variety of applications due to its attractive photophysical characteristics. Nevertheless, its employment as a fluorescent probe for temperature sensing has been barely reported. In this contribution, we investigated the phase transition of poly(2-(2-methoxyethoxy)ethyl methacrylate) [P(MEO2 MA)] and poly[oligo(ethylene glycol) methyl ether methacrylates] [P(OEGMA300 and OEGMA500 )], end-functionalized with a fluorescent anthrapyrazolone moiety [7-chloro-2-(2-hydroxyethyl) dibenzo[ cd, g ]indazol-6(2 H )-one] (Cl-dye-OH) in aqueous solutions for the development of fluorescent polymeric thermometers. A fluorescence investigation revealed that P(MEO2 MA) displays nearly 100% fluorescence quenching above its T CP, making it suitable as a sensor for a critical temperature, while the fluorescence intensity of the P(OEGMA) copolymers decreases gradually with increasing temperature, showing their promising potential for application as fluorescent thermometers. In vitro cytotoxicity tests on DC2.4 cells showed that none of the polymers were cytotoxic at the low concentrations that are used for sensing applications ( i.e., 10 and 100 ng mL −1 ). Unexpectedly, the P(OEGMA)-based fluorescence thermometers have a very broad sensing regime that spans the whole liquid water temperature range, which is significantly broader than the sharp LCST phase transition that usually spans only 10 °C. These polymers may be used to assess intracellular temperature since their fluorescence intensity decreases linearly with temperature. In contrast, P(MEO2 MA) can be used as a fluorescent probe to sense whether the temperature is below or above 25 °C. These polymeric temperature sensors are promising for future development of probes for intracellular temperature measurements.